The Effect of Reproductive Health Counseling to the Perception on Prevention Behavior of Leucorrhea in Female Students at SMAN 1 Temon (Based on the Health Belief Model/HBM Theory) - Beti Wulansari; Wahyudi Istiono; Shinta Prawitasari (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
ABSTRACTBackground: Leucorrhea is a problem that is often experienced by women. Female adolescents have inadequate knowledge about handling and preventing leucorrhea. This inadequate knowledge has an impact on the perception that leucorrhea will not affect their health. But in reality, for the last 3 (three) years from 2014 to 2016, there was an increase in complaints according to the screening results by Puskesmas Temon 2 (Community Health Center). Because of this reason, interventions are needed regarding the knowledge about leucorrhea prevention applying the Health Belief Model (HBM) theory, including perceptions of seriousness, vulnerability, benefits, obstacles, and impulse to act that can be measured by a perceptual score.Objectives: This study aimed to determine the effect of reproductive health counseling on the perceptual score of seriousness, vulnerability, benefits, obstacles, and impulse to act involving female students’ perceptions in leucorrhea prevention behavior of SMAN 1 Temon (Senior High School) before and after health counseling. The score was measured by the HBM.Methods: The research was a quasi-experimental study with a time series design. The population of this research was the female students of class X and XI SMAN 1 Temon. The sample consisted of 55 female students who had fulfilled the inclusion and exclusion criteria by using simple random sampling technique. Data were analyzed using eepeated ANOVA test with significance level (α) of 0.05.Results: The results of this study indicated that there were significant differences in perception scores (p = 0.000) before counseling and after counseling in perceptions of seriousness in prevention, vulnerability to leucorrhea, benefits in prevention, barriers to preventive action, encouragement to act and total HBM score. Conclusions: Reproductive health counseling about leucorrhea based on the Health Belief Model theory is effective to improve female adolescent students' perception in taking action to prevent leucorrhea, especially in perception scores of seriousness, vulnerability, benefits, obstacles, and impulse to act in leucorrhea prevention behavior of female students in SMAN 1 Temon.